PENYELESAIAN PERKARA DI LUAR PENGADILAN DI DALAM KONDISI DUALISME PEMERINTAHAN DESA - Yandi Utami, Luh Putu; P. Windia, Wayan; Sudantra, I Ketut (Kertha Desa; Vol. 01, No. 03, September 2013)
With the enactment of Law Number 32 of 2004 which repealed the Act Number 22 of 1999 arising “the Vacuum of Law” in the foundation as well as in the implementation of village administration in Bali. On the one hand the Act Number 22 of 1999 was repealed, while the Law Number 32 Year 2004 not yet effective in Bali. In such “Vacuum of Law”, arose the polemic regarding the expected model or ideal format of villages held in Bali, which institutions should contribute to resolve cases that occurred in the village in a state of institutional dualism of village administration which is occurring in society and determined by their customary law, the form of out of court settlement in the customary dispute resolved by consensus agreement of peace through the customary laws. How is the effectiveness of out of court settlement in the village to resolve the customary disputes through the justice of the village peace by deliberation? In writing this article, the method used is the method of empirical research. Empirical legal research conceptualized as an empirical phenomenon that can be observed in real life. Settling disputes out of court by a justice of the peace in the village of indigenous people in Bali can be resolved peace and deliberation. The conclusion of the extrajudicial settlement in the village administration dualism conditions can be settled amicably without having to go through judicial mechanisms.
Keywords: Customary Disputes, Justice of the Village Peace